A Three in One Strategy to Achieve Zirconium Doping, Boron Doping, and Interfacial Coating for Stable LiNi0.8Co0.1Mn0.1O2 Cathode. Issue 2 (27th November 2020) - Feng, Ze; Rajagopalan, Ranjusha; Zhang, Shan; Sun, Dan; Tang, Yougen; Ren, Yu; Wang, Haiyan
Abstract: LiNi0.8 Co0.1 Mn0.1 O2 cathodes suffer from severe bulk structural and interfacial degradation during battery operation. To address these issues, a three in one strategy using ZrB2 as the dopant is proposed for constructing a stable Ni‐rich cathode. In this strategy, Zr and B are doped into the bulk of LiNi0.8 Co0.1 Mn0.1 O2, respectively, which is beneficial to stabilize the crystal structure and mitigate the microcracks. Meanwhile, during the high‐temperature calcination, some of the remaining Zr at the surface combined with the surface lithium source to form lithium zirconium coatings, which physically protect the surface and suppress the interfacial phase transition upon cycling. Thus, the 0.2 mol% ZrB2 ‐LiNi0.8 Co0.1 Mn0.1 O2 cathode delivers a discharge capacity of 183.1 mAh g −1 after 100 cycles at 50 °C (1C, 3.0–4.3 V), with an outstanding capacity retention of 88.1%. The cycling stability improvement is more obvious when the cut‐off voltage increased to 4.4 V. Density functional theory confirms that the superior structural stability and excellent thermal stability are attributed to the higher exchange energy of Li/Ni exchange and the higher formation energy of oxygen vacancies by ZrB2 doping. The present work offers a three in one strategy to simultaneously stabilize the crystal structure and surface for the Ni‐rich cathode via a facile preparation process. Abstract : A three in one strategy using ZrB2 dopant modification is proposed for constructing stable LiNi0.8 Co0.1 Mn0.1 O2 cathodes. The structural and interfacial stability of the material can be improved owing to the Zr and B doping in the bulk and the formation of lithium zirconium oxide coating layer. This strategy provides rational guidance for designing high‐performance Ni‐rich cathode materials.